PENGARUH KUALITAS SISTEM, KUALITAS INFORMASI, KUALITAS LAYANAN, TERHADAP KEPUASAN PENGGUNA SISTEM INFORMASI AKADEMIK UNIVERSITAS MERDEKA MALANG - Listanto Tri Utomo; Yusaq Tomo Ardianto; Nanik Sisharini (Jurnal Teknologi dan Manajemen Informatika, 2017)
The aims of this article are making explanation on any variables introduced by DeLone and McLean (2003), such as system quality, information quality, service quality, individual impact organization impact, and net benefit. These variables were implemented to the academic information system (SIAKAD) in Universitas Merdeka Malang. By quantitative research, the impact of these variables to the users satisfication will be known. And also, what variable be a most affecting in this system.DOI: https://doi.org/10.26905/jtmi.v3i2.1425